Method for improving biocompatibility of porous implant

By sonicating and anodizing the porous implant, residual powder is removed and micro-nano-scale surface patterns are generated, the problem of insufficient biocompatibility of the porous implant is solved, and the biocompatibility and cell interaction effect of the implant are significantly improved.

CN119980410APending Publication Date: 2025-05-13SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938163.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-05-13

AI Technical Summary

Technical Problem

The existing porous implants manufactured by additives are weak in biocompatible, which can easily lead to inflammatory responses and bone damage reabsorption, which ultimately leads to loosening and even failure of the implant.

Method used

By performing the porous implants with a first ultrasonic treatment, anodization treatment and a second ultrasonic treatment, residual powder in the deep area is removed and a stable micro-nano-scale surface pattern is generated.

Benefits of technology

It significantly improves the biocompatibility of porous implants, promotes the adhesion of osteoblasts and the mineralization process of cells, and enhances the interaction between the implant and cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119980410A_ABST
    Figure CN119980410A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of porous materials, and discloses a method for improving the biocompatibility of a porous implant. The method comprises the following steps: carrying out first ultrasonic treatment on a porous implant made of a stainless steel material; the porous implant subjected to ultrasonic treatment is placed in an anodic oxidation electrolyte containing ammonium fluoride, and anodic oxidation treatment is conducted at the constant temperature and the constant pressure; and carrying out second ultrasonic treatment on the porous implant subjected to anodic oxidation. The porous implant is modified by using a reverse high-voltage anodic oxidation method, and residual surface powder is removed. After anodic oxidation treatment, low-frequency ultrasound is applied to further destroy the structures, so that removal of residual powder in a deep area of the porous implant is promoted, and a new and stable micro-nano surface pattern is generated. The newly generated micro-nano surface pattern is beneficial to the adhesion of osteoblasts, the mineralization process of the cells can be obviously promoted, the interaction between the cells and the implant is promoted, and the biocompatibility of the porous implant is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous materials, and in particular to a method for improving the biocompatibility of a porous implant. Background Art

[0002] Additive Manufacturing (AM), also known as 3D printing, is a research hotspot in contemporary near-net-shape technology and is constantly driving the innovation of the manufacturing industry. At present, AM technology has been initially applied to high-end manufacturing fields such as aerospace, nuclear power, automobile manufacturing, and biomedicine. In particular, Selective Laser Melting (SLM) has attracted great attention from the scientific research and industrial circles due to its unique advantages in near-net-shape shaping and personalized customization of metal implants.

[0003] With the continuous development of AM technology, the rapid and precise manufacturing of porous implants with complex shapes has become possible, which effectively solves the forming problem of complex and special-shaped structural parts, simplifies the processing procedures and shortens the processing cycle. However, within the set pore size range, porous implants manufactured by SLM often retain a large amount of loose powder and incompletely melted unmelted powder, which increases the risk of loose powder falling off the surface after implantation, which may cause inflammatory reactions and bone damage resorption, and ultimately lead to implant loosening and even failure. In other words, the existing implants manufactured by additive manufacturing have weak biocompatibility.

[0004] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a method for improving the biocompatibility of porous implants. The purpose is to promote the removal of residual powder in the deep area of ​​the porous material by surface treatment of the porous implant and generate a new and stable micro-nanoscale surface pattern to improve the biocompatibility of the porous implant.

[0006] The above object of the present invention is achieved through the following technical solution: a method for improving the biocompatibility of a porous implant, wherein the method comprises the following steps:

[0007] performing a first ultrasonic treatment on the porous implant made of stainless steel;

[0008] placing the porous implant after ultrasonic treatment in an anodic oxidation electrolyte containing ammonium fluoride, and performing an anodic oxidation treatment at a constant temperature and pressure;

[0009] The porous implant body that has completed anodization is subjected to a second ultrasonic treatment.

[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0011] As a preferred technical solution, in the method for improving the biocompatibility of a porous implant, the ultrasonic frequency of the first ultrasonic treatment is 20-25 kHz, and the ultrasonic time is 15-30 min.

[0012] As a preferred technical solution, in the method for improving the biocompatibility of a porous implant, the ammonium fluoride-containing anodic oxidation electrolyte comprises 0.5-0.7 wt % ammonium fluoride, 93-97 % (v / v) ethylene glycol and 3-7 % (v / v) water.

[0013] As a preferred technical solution, in the method for improving the biocompatibility of a porous implant, the voltage of the anodizing treatment is 90-120V and the current is less than 2A.

[0014] As a preferred technical solution, in the method for improving the biocompatibility of porous implants, the temperature of the anodizing electrolyte is lower than 40°C.

[0015] As a preferred technical solution, in the method for improving the biocompatibility of a porous implant, the ultrasonic frequency of the second ultrasonic treatment is 20-25 kHz, and the ultrasonic time is 10-30 min.

[0016] As a preferred technical solution, in the method for improving the biocompatibility of a porous implant, a micro-nano structure is formed on the surface of the porous implant after the second ultrasonic treatment.

[0017] As a preferred technical solution, in the method for improving the biocompatibility of porous implants, the micro-nano structure includes a corrugated micro-nano structure, a fish-scale micro-nano structure and a dendritic micro-nano structure.

[0018] As a preferred technical solution, in the method for improving the biocompatibility of a porous implant, after the porous implant is subjected to the second ultrasonic treatment, the pore size of the porous implant is 300-500 μm.

[0019] As a preferred technical solution, the method for improving the biocompatibility of a porous implant is characterized in that the porous implant is a 316L austenitic stainless steel porous implant produced by 3D printing.

[0020] Beneficial effects: Compared with the prior art, the present invention utilizes a reverse high-voltage anodizing method to modify the porous implant, removes the residual surface powder, and creates a disordered, large-diameter, deep, and weakly bonded "inverted cone" honeycomb tubular structure. After anodizing, low-frequency ultrasound is applied to further destroy these structures, promote the removal of residual powder in the deep region of the porous implant, and generate a new, stable micro-nanoscale surface pattern. The newly generated micro-nanoscale surface pattern facilitates the adhesion of osteoblasts, and can significantly promote the mineralization process of cells, promote the interaction between cells and implants, and thus improve the biocompatibility of porous implants. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the micro-nanoscale texture formed on the surface of a porous 316L stainless steel sample after high-pressure anodizing and polishing;

[0022] Figure 2 This is the structural diagram of the porous 316L stainless steel compression specimen;

[0023] Figure 3 The compressive stress-strain curves of porous 316L stainless steel compression specimens before and after polishing;

[0024] Figure 4 This is the real-time interface diagram of the porous 316L stainless steel compression specimen before and after polishing;

[0025] Figure 5 The SEM surface morphology of porous 316L stainless steel in vitro biomedical specimens before and after polishing;

[0026] Figure 6 This is the surface roughness diagram of porous 316L stainless steel in vitro biomedical specimens before and after polishing;

[0027] Figure 7 This is a graph showing the effect of porous 316L stainless steel in vitro biomedical specimens before and after polishing on the proliferation of mouse embryonic osteoblast precursor cells;

[0028] Figure 8 Alizarin red staining of the surface ECM of porous 316L stainless steel in vitro biomedical specimens before and after polishing;

[0029] Fig. 9 This is a semi-quantitative result of cell mineralization induced by porous 316L stainless steel in vitro biomedical specimens before and after polishing. DETAILED DESCRIPTION

[0030] The present invention provides a method for improving the biocompatibility of a porous implant. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementation methods. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and do not mean a necessary sequence, unless otherwise specified that a certain sequence must be followed. The serial numbers themselves, such as "first", "second", etc., assigned to the components herein are only used to distinguish the objects described and do not have any order or technical meaning.

[0032] The present invention provides a method for improving the biocompatibility of a porous implant, comprising the following steps:

[0033] S10, performing a first ultrasonic treatment on the porous implant made of stainless steel.

[0034] Specifically, the porous implant is a porous bone implant designed and manufactured using additive manufacturing. Of course, it can also be other implants. The additive manufacturing technology can be used to prepare porous implants with more complex structures. The stainless steel is 316L austenitic stainless steel, which has the characteristics of moderate price, easy availability, good formability, plasticity, corrosion resistance and biocompatibility. The porous implant is placed in a low-frequency ultrasound machine, and the ultrasound frequency can be 20kHz, 21kHz, 22kHz, 23kHz, 24kHz, 25kHz, and the ultrasound is applied for 15min to 20min, 20min to 25min, and 25min to 30min to remove the residual powder that is not firmly bonded to the pores and the pore surface. In other words, the porous implant can be first subjected to ultrasonic treatment to remove the residual powder attached to it, and this step can be regarded as pretreatment.

[0035] S20, placing the porous implant after ultrasonic treatment in an anodic oxidation electrolyte containing ammonium fluoride, and performing an anodic oxidation treatment at a constant temperature and pressure.

[0036] Specifically, the porous implant is fixed by the anode clamp of the anodizing equipment and placed in the anodizing electrolyte of ammonium fluoride, the magnetic stirring device is started and the anodizing parameters are set for anodizing. Among them, the electrolyte includes 0.5-0.7wt% ammonium fluoride, 93-97% (v / v) ethylene glycol and 3-7% (v / v) water. Ammonium fluoride can effectively etch the surface of the porous implant made of stainless steel and generate its nano honeycomb tubular structure. Ethylene glycol can regulate the rate and quality of the anodized film. Ethylene glycol has high viscosity and conductivity, which contributes to the stability of the electrolyte. Furthermore, ethylene glycol can preferentially reduce the polarization of the electrolyte, improve the efficiency of oxidation, appropriately slow down the etching efficiency of ammonium fluoride, and ensure the smooth oxidation reaction and etching of the electrolyte.

[0037] In the present invention, the anodizing parameters are: the power supply is set to constant voltage mode, the voltage is 90-120V, the current setting cannot exceed 2A, and the electrolyte temperature is maintained below 40°C; in existing anodizing, low voltage is often used to generate nanotubular structures, most of which are used to generate micro-nano structures on the surface of the block and maintain their structural stability. The purpose of the high voltage in the present invention is to accelerate the etching rate so that the etching rate is greater than the oxidation rate. Combined with the unstable characteristics of the surface oxide film of stainless steel, the electrolyte temperature is kept constant, and finally an "inverted cone" nanotubular structure with a large outer diameter and a small inner diameter is generated. That is, it is convenient to remove its unstable structure, and at the same time, its root texture structure can be basically retained. For this reason, the reaction can be better coordinated within the voltage and current range. If the voltage, current or electrolyte temperature is too high, it is basically corrosion, which is extremely unstable and causes great damage to the sample.

[0038] In the present invention, high pressure anodizing (AO) treatment, the specific details of the principle are as follows:

[0039] (i) Formation of barrier layer: Under high voltage, when the AO process begins, a barrier layer will immediately form and thicken on the surface of the material to prevent voltage breakdown. This process is manifested by the following reactions:

[0040]

[0041] (ii) Formation and growth of honeycomb pits: As the voltage increases, the barrier layer undergoes random breakdown, triggering electrochemically assisted chemical dissolution in the electrolyte, forming honeycomb pits. As these pits deepen, the newly formed oxide layer continues to thicken and the local electric field strength increases. Under high pressure conditions, further chemical dissolution promotes the formation of nanotubular oxide layers. The dissolution of these oxides in fluorinated electrolytes can be described by the following reaction:

[0042] Fe2O3+6H + +12F- →2[FeF3] 3- +3H2O

[0043] Cr2O3+6H + +12F - →2[CrF3] 3- +3H2O

[0044] NiO+2H + +3F - →[NiF3] 3- +H2O

[0045] (iii) Dynamically evolving nanostructures: Under continuous high pressure conditions, the increase in temperature, current density, and polarization causes the dissolution rate of the nanotubes to exceed the oxidation rate, thereby hindering the dynamic equilibrium. This imbalance leads to an increase in the outer diameter and depth of the nanotube structure.

[0046] (iv) Detachment of nanotube structure: After 50 minutes of anodization, the walls between adjacent nanotubes on the inner and outer surfaces of the porous material become thinner and thinner, especially on the upper surface. During the magnetic stirring of the electrolyte, the formed structure will eventually fall off, and the bond between the residual powder and the substrate will become looser. This process is conducive to removing most of the residual powder.

[0047] S30, performing a second ultrasonic treatment on the porous implant that has completed anodization.

[0048] The porous implant after anodization in step S20 is placed in a low-frequency ultrasonic device again for secondary ultrasonic treatment at an ultrasonic frequency of 20-25 kHz for 15-30 minutes. Figure 1 After the ultrasonic treatment, nearly 95-97% of the residual powder in the porous stainless steel implant was removed, and the inner and outer surfaces of the holes were relatively smooth and formed corrugated, fish-scale and dendritic texture structures.

[0049] The removal of residual powder inside and on the surface of the porous body and the micro-nanoscale texture generated on the surface provide a more favorable environment for cell growth, attachment and mineralization. These features simulate the natural extracellular matrix and strengthen cell anchoring and signal transduction. Furthermore, the reduction of surface roughness to a certain extent can also help cells adhere and extend inside the pores, significantly enhancing the biological function of bone tissue cells.

[0050] The above technical solution provided by the present invention is further explained below through specific embodiments.

[0051] Example 1

[0052] This example prepares a polished porous 316L compression sample, and the specific process is as follows:

[0053] The porous 316L stainless steel compression specimen was made into a cylinder according to the international standard BS ISO 13314-2011 (e.g. Figure 2 As shown in the figure, a disc with a diameter of 6mm×1mm is placed at both ends to ensure the stability of the sample during the test. A cut edge (200μm) is provided at the lower end of the disc. A compression test section (4mm×9mm) is located between the two discs. The unit cell of the Gyroid porous structure of the test section is set to 2.5mm×2.5mm×2.5mm, and the porosity is set to 70% to ensure that the interior of the porous material is through-hole.

[0054] use The porous 316L compressed sample designed by the 125HL printer was 3D printed. After printing, the compressed sample was subjected to 25kHz low-frequency ultrasound along the manufacturing direction for 20 minutes to remove the residual powder that was not firmly bonded inside the pores and on the pore surface.

[0055] The porous 316L stainless steel compression sample was fixed by an anode clamp and placed in an ammonium fluoride anodic oxidation electrolyte (0.6wt% ammonium fluoride, 93% (v / v) ethylene glycol and 7% (v / v) water). The power supply was set to a constant voltage mode with a voltage of 90V and a current setting not exceeding 2A. The oxidation process was stirred throughout and the electrolyte temperature was kept below 40°C. The anodic oxidation time was 50min.

[0056] The porous 316L stainless steel compression sample after anodization was cleaned with distilled water, and the sample was placed in a 25kHz low-frequency ultrasonic machine for 20 minutes to vibrate and ultrasonicate, which deeply destroyed the structure generated by anodization and removed more residual powder inside and outside the pores. After vibration, a porous 316L stainless steel compression sample (316L-AU) with a smooth and bright surface was obtained.

[0057] Under room temperature conditions, compression tests were conducted using an Instron 68TM-30 double-column electronic tensile testing machine equipped with a 30 kN load at a rate of 0.2 mm / min. The compression test ended when the stress dropped by more than 50% or the sample approached a dense solid state. During this process, a high-definition digital microscope was used to monitor the porous 316L and polished porous 316L-AU specimens in real time.

[0058] The compressive stress-strain curves of porous 316L stainless steel before and after polishing are shown in Figure 2. Figure 3As shown, three samples of each set of printing parameters were compressed along the direction parallel to the build direction. For the unpolished porous 316L, the elastic modulus, yield strength, ultimate compressive strength, platform stress, energy absorption and elongation were 5.47GPa, 81.92MPa, 2109.75MPa, 164.08MPa, 83.18MJ / m3 and 94.36%, respectively. The sample formed a solid cylindrical morphology after compression.

[0059] pass Figure 4 The compression effect screenshots show that the surface texture of the polished porous 316L compression sample is significantly improved under 90V high-voltage anode polishing conditions, and it is more rounded and smooth after polishing. In addition, the polished porous 316L-AU also shows a similar trend in the compression test, and the specific results are listed in the following table:

[0060]

[0061] In contrast, the elastic modulus, yield strength, ultimate compressive strength, platform stress and energy absorption values ​​of polished 316L-AU-50 are 5.31GPa, 79.91MPa, 2025.42MPa, 168.65MPa, 85.48MJ / m3 and 91.82%, respectively. The comparison results show that although the mechanical comprehensive properties of the polished compression sample are slightly reduced, its platform stress is still improved, and the overall performance is still in line with the mechanical requirements of bone tissue. It is particularly noteworthy that the energy absorption value has not decreased but increased, which is crucial for the impact buffering capacity of porous materials and helps to achieve better protection of bones. This is mainly attributed to the following two reasons: According to the polishing mechanism, most of the residual powder and oxidation coating are removed, the pore size is enlarged by 30-50μm relative to the original, and the damage to the wall of the 316L porous scaffold is small. In addition, the texture structure generated on the surface reduces the roughness of the material, which can disperse the stress during the compaction process and further slow down the damage to the sample. During the low-frequency ultrasonic process, the surface stress concentration of 3D printed 316L stainless steel can be effectively improved and the stress can be dispersed, which leads to a steady increase in compressive stress.

[0062] Example 2

[0063] This example prepares a polished porous 316L stainless steel in vitro biomedical specimen, and the specific process is as follows:

[0064] The porous 316L stainless steel in vitro biomedical specimen is set as a cylinder with a diameter of 10 mm × 1 mm, the unit cell of the Gyroid porous structure is set to 2.5 mm × 2.5 mm × 2.5 mm, and the porosity is set to 70% to ensure that the interior of the porous material is through-hole.

[0065] use The 125HL printer was used to 3D print the porous 316L in vitro biomedical specimens designed by the company. After printing, the compressed specimens were subjected to 25kHz low-frequency ultrasound along the manufacturing direction for 15 minutes to remove residual powder that was not firmly bonded to the pores and the pore surface.

[0066] The porous 316L in vitro biomedical specimen was fixed by an anode clamp and placed in an ammonium fluoride anodic oxidation electrolyte (0.5wt% ammonium fluoride, 94% (v / v) ethylene glycol and 6% (v / v) water). The power supply was set to a constant voltage mode with a voltage of 90V and a current setting not exceeding 5A. The oxidation process was stirred throughout and the electrolyte temperature was kept below 40°C. The anodic oxidation time was 40min.

[0067] The porous 316L in vitro biomedical specimen after anodization was cleaned with distilled water, and the specimen was placed in a 25kHz low-frequency ultrasonic machine for 15 minutes to vibrate and ultrasonicate, which deeply destroyed the structure generated by anodization and removed more residual powder inside and outside the pores. After vibration, a porous 316L stainless steel in vitro biomedical specimen (316L-AU) with a smooth and bright surface was obtained.

[0068] The surface morphology of porous 316L and 316L-AU samples was characterized by scanning electron microscopy (SEM). Figure 5 As shown). For the 316L sample, a low-frequency ultrasonic treatment was carried out for 15 minutes before the test. Although most of the residual powder that is easy to fall off was removed, a large amount of residual powder can still be observed under SEM, and many loose unmelted powder particles can be seen under magnification. It is worth noting that the overall texture of the porous wall of the 316L-AU sample that has been treated with high-pressure anodizing and low-frequency ultrasonic treatment is relatively smooth and flat, and the removal of residual powder has been significantly improved. Although there is still a small amount of residue in some areas, it is basically some unmelted powder with a specific structure. Under low magnification, some small black holes can be seen, which are usually formed by the fall-off of some unstable unmelted powder after anodizing and then low-frequency ultrasonic vibration, further reducing the residue of unmelted powder. After high magnification, it was found that the inside and outside of the pore wall showed three structures, namely corrugated, fish scale and dendritic textures, and these textures are regular, stable and orderly.

[0069] Compared with the porous 316L sample, the roughness of the porous 316L-AU sample showed obvious differences under electron microscopy. According to the test results (such as Figure 6 The 2D and 3D morphology of the surface roughness of the two porous samples are basically consistent with the texture structure observed by SEM. The roughness of the 316L-AU sample is significantly reduced, with regular undulations. In addition, the micron-scale texture structure on its surface has a certain promoting effect on cell growth.

[0070] Mouse embryonic osteoblast precursor cells (MC3T3-E1) were cultured at a rate of approximately 5 × 10 4 Cells were inoculated into a porous 316L stainless steel cylindrical sample at a density of 10 cells / well and after culturing for 1, 3 and 5 days, the original culture medium was removed and a new culture medium containing 10% volume ratio Cell counting kit 8 (CCK8, Shanghai Yisheng Biotechnology Co., Ltd, China) was added for incubation for 1 hour, and then the reduced water-soluble yellow formazan was taken out and placed in a 96-well plate. The absorbance value of each well was measured at a wavelength of 450 nm using an ELISA reader (IMark, BIO-RAD, China) to evaluate its cell proliferation. Figure 7 As shown, on the first day, the absorbance of 316L-AU was slightly higher than that of 316L, but there was basically no difference. On days 3 and 5, especially on day 5, the 316L-AU sample showed excellent cell proliferation rate, and the difference gradually emerged, which further verified that the polishing technology can effectively improve the biocompatibility of the sample. The reason why the 316L-AU sample has such good cell activity is mainly attributed to the removal of residual powder inside and on the surface of the porous body and the micro-nanoscale texture generated on the surface, which provides a more favorable environment for cell diffusion, attachment and growth. These features simulate the natural extracellular matrix and enhance cell anchoring and signal transduction. In addition, a certain degree of reduction in surface roughness can also help cells adhere and extend inside the pores.

[0071] To evaluate the long-term osteogenic capacity of MC3T3-E1 cells, extracellular matrix (ECM) mineralization analysis was visualized by Alizarin Red S (ARS, Solarbio, China) staining. MC3T3-E1 cells were plated at 5 × 10 4 The cells were seeded on the porous samples at a density of 10 cells / mL and cultured at 37°C for 21 days using osteogenic DMEM medium containing 10 mM L-1β-glycerophosphate sodium, 0.3 mM L-1α-ascorbic acid and 100 nM L-1 dexamethasone. After the culture, the mineralized cells on the porous samples were washed with PBS, fixed with 4% formaldehyde for 15 minutes, and then stained with ARS (2%, pH = 4.3, 500 μL per well) at room temperature for 5 minutes. Rinse with deionized water to remove unbound staining, and observe the mineralized nodules under an optical microscope (MCK-50MC, Caikon, China). Finally, 10 w / v% cetylpyridinium chloride was used to dissolve the bone mineralized calcium nodules for 15 minutes, and the absorbance of the resulting solution at 562 nm was measured and semi-quantitatively analyzed. In the stained pictures, the dark red area indicates more mineral deposition, which also means that the cells induced by the sample are more mature. As Figure 8 As shown in a and b, compared with 316L, 316L-AU samples have more and larger dark red areas on the surface and in the pores, and more mineralized nodules are generated. Figure 8 In c and d, we can clearly see that on the porous sample of 316L, the calcium nodules are mainly deposited in the printed defective grooves. On the sample of 316L-AU, we can see that many calcium nodules are deposited and wrapped around the bracket, like a thin film coated on it ( Figure 8 d in the figure). Its color is also blood red, which is darker than that of 316L, and its semi-quantitative result is the same as the staining result ( Fig. 9 ), further indicating that the polished 316L-AU sample can significantly promote the matrix mineralization of osteoblasts. This improvement may be due to the "fish scale-like" micro-nano structure creating a bionic microenvironment that is more conducive to cell function, thereby stimulating the differentiation of osteoblasts. At the micro-nano scale, the interaction between cells and material surfaces becomes more complex, and the micro-nano structure activates specific receptors on the cell membrane, such as integrins. This activates downstream signaling pathways, including the BMP2 pathway, thereby promoting osteogenic differentiation and enhancing the bone bonding ability of the implant. In addition, the reduction of ions released by the oxide film mitigates potential cytotoxic effects and creates a stable interface for long-term implant integration. These synergistic effects emphasize the importance of optimizing surface morphology to improve biological performance. The formation of micro-nano structures on porous 316L implants that have been polished by high-pressure anodizing can significantly enhance the biological functions of bone tissue cells.

[0072] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for improving the biocompatibility of a porous implant, characterized in that: The method comprises the following steps: performing a first ultrasonic treatment on the porous implant made of stainless steel; placing the porous implant after ultrasonic treatment in an anodic oxidation electrolyte containing ammonium fluoride, and performing an anodic oxidation treatment at a constant temperature and pressure; The porous implant body that has completed anodization is subjected to a second ultrasonic treatment.

2. The method for improving the biocompatibility of a porous implant according to claim 1, characterized in that: The ultrasonic frequency of the first ultrasonic treatment is 20-25 kHz, and the ultrasonic time is 15-30 min.

3. The method for improving the biocompatibility of a porous implant according to claim 1, characterized in that: The ammonium fluoride-containing anodic oxidation electrolyte comprises 0.5-0.7 wt % of ammonium fluoride, 93-97 wt % (v / v) of ethylene glycol and 3-7 wt % (v / v) of water.

4. The method for improving the biocompatibility of a porous implant according to claim 1, characterized in that: The voltage of the anodizing treatment is 90-120V, and the current is less than 2A.

5. The method for improving the biocompatibility of a porous implant according to claim 4, characterized in that: The temperature of the anodizing electrolyte is lower than 40°C.

6. The method for improving the biocompatibility of a porous implant according to claim 1, characterized in that: The ultrasonic frequency of the second ultrasonic treatment is 20-25 kHz; the ultrasonic time is 10-30 min.

7. The method for improving the biocompatibility of a porous implant according to claim 1, characterized in that: After the second ultrasonic treatment, a micro-nano structure is formed on the surface of the porous implant.

8. The method for improving the biocompatibility of a porous implant according to claim 7, characterized in that: The micro-nano structure includes a corrugated micro-nano structure, a fish-scale micro-nano structure and a dendrite-like micro-nano structure.

9. The method for improving the biocompatibility of a porous implant according to claim 7, characterized in that: After the porous implant is subjected to the second ultrasonic treatment, the pore size of the porous implant is 300-500 μm.

10. The method for improving the biocompatibility of a porous implant according to claim 1, characterized in that: The porous implant is a 316L austenitic stainless steel porous implant produced by 3D printing.